2013
DOI: 10.1002/cbin.10084
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal transplantation of bone marrow‐derived mesenchymal stem cells reduced airway inflammation and up‐regulated CD4+CD25+ regulatory T cells in asthmatic mouse

Abstract: Mesenchymal stem cells attenuate the severity of lung injury due to their immunomodulatory properties. The effect of bone marrow-derived mesenchymal stem cells on asthma is seldom reported. We have examined the effect of BMSCs on airway inflammation in asthma. Forty female BALB/c mice were equally randomised into PBS group, BMSCs treatment group, BMSCs control group and asthmatic group. Reactivity of the airway to acetylcholine was measured by barometric plethysmography. Cytokine profiles of bronchoalveolar la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
2
22
1
Order By: Relevance
“…No significant effect was seen in 3 other studies [12,15,19]. MSC treatment before sensitization [21], before allergen challenge [24] and after allergen challenge [18] led to a significant increase in BAL IL-10 levels (P < 0.05) in 3 studies, whereas no significant change was noted in 4 studies [9,12,13,23] that used MSC treatment before [9,13,23] and after [12] allergen challenge.…”
Section: Other Biochemical Outcomescontrasting
confidence: 45%
See 3 more Smart Citations
“…No significant effect was seen in 3 other studies [12,15,19]. MSC treatment before sensitization [21], before allergen challenge [24] and after allergen challenge [18] led to a significant increase in BAL IL-10 levels (P < 0.05) in 3 studies, whereas no significant change was noted in 4 studies [9,12,13,23] that used MSC treatment before [9,13,23] and after [12] allergen challenge.…”
Section: Other Biochemical Outcomescontrasting
confidence: 45%
“…No significant effect was seen in 2 studies, including the Lathrop et al study [9,13]. MSC treatment led to a significant decrease in BAL IL-13 levels in 3 studies [9,15,17] (P < 0.001 to P < 0.05), including with treatment after allergen challenge [15], whereas BAL IL-13 levels were already low in controls in 1 study [25] and there was no significant change in 5 studies [12,13,20,23,24]. One short-term study that reported on IL-9 levels in BAL found a reduction with MSC treatment (P < 0.05) [26].…”
Section: Other Biochemical Outcomesmentioning
confidence: 62%
See 2 more Smart Citations
“…+ regulatory T cells play a significant role in inducing immune tolerance of the graft (Ge et al, 2013). This can be achieved by modulating T cell proliferation as well as by regulating the type and quantity of T cell secretions.…”
Section: Discussionmentioning
confidence: 99%